2022
DOI: 10.3390/ijerph192114479
|View full text |Cite
|
Sign up to set email alerts
|

Remote Learning in Higher Education: Evidence from Poland

Abstract: The COVID-19 pandemic has brought about a sudden transformation at universities. The previous mode of teaching has been replaced by remote education, the effectiveness of which depends, among other things, on the technological infrastructure of universities and the digital competence of lecturers and students. The main objective of this study is to evaluate remote learning in higher education from the students’ point of view. The uniqueness of the present research approach lies in the identification of four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…In turn, Becker (1994) stated that investment in human capital is a form of resource allocation that affects future real income. By investing in human capital, he meant, among other things, education, gaining experience on the job and training (Aghion & Howitt, 1997;Becker, 1962;Fredman, 2014;Grossman & Helpman, 1990;Ober & Kochmańska, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In turn, Becker (1994) stated that investment in human capital is a form of resource allocation that affects future real income. By investing in human capital, he meant, among other things, education, gaining experience on the job and training (Aghion & Howitt, 1997;Becker, 1962;Fredman, 2014;Grossman & Helpman, 1990;Ober & Kochmańska, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The bibliometric review method is suitable for addressing the research questions posed because of its ability to quantify the impact and trends of research in a specific field [12,13]. This method allows for a thorough analysis of the literature to identify trends, shifts in research focus, and underexplored areas [14][15][16][17]. Despite the growing literature on digital competencies in open innovation, there is a gap in how these competencies have evolved and how they are integrated in different contexts and sectors [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Parker et al [16] found that approximately 80% of the students, who took online courses during the pandemic, did not actively participate in the online course activity. Ober and Kochmanska [17] reported that many students experienced distraction and decreased concentration in the process of online learning. This means that the objective indicators may not be matched by students' subjective perception of engagement.…”
Section: Introductionmentioning
confidence: 99%